Microstructures and performance of CaO-based ceramic cores with different particle size distributions for investment casting. (6th February 2018) - Zhou, P P; Wu, G Q; Tao, Y; Cheng, X; Zhao, J Q; Nan, H
Abstract: A series of calcium-based ceramic cores for casting titanium alloy were prepared by mixing different amounts of coarse and fine powders through injection molding. The effects of particle size on the microstructures and properties of the ceramic cores were investigated using quantitative and statistical analysis methods. It is found that the shrinkage and room-temperature strength of the ceramic cores were enhanced as increasing the contents of fine particles. Moreover, the creep resistance of the ceramic cores increased initially and then decreased. The increase in the fine particle content of the cores reduced the number and mean diameter of pores after sintering. The grain boundary density decreased firstly and then increased. The flexural strength of the ceramic cores at room temperature decreased with increasing porosity of ceramic cores, whereas the creep resistance increased with decreasing grain boundary density. A core exhibiting the optimal property was obtained when mixing 65 wt% of coarse powders (75–150 μ m) and 35 wt% of fine powders (25–48 μ m).